Biodiversidad y ecología de los anfípodos hiperideos del Mar Argentino y aguas adyacentes: Themisto gaudichaudii, una especie clave. - Padovani, L.N. (Universidad Nacional de Mar del Plata. Facultad de Ciencias Exactas y Naturales, 2013)
Biodiversity of hyperiid amphipods was studied for Argentine Sea and adjacent waters (27° and 55° S). Additionally, ecological aspects of the prominent species, Themisto gaudichaudii, were analyzed. A database including 1001 zooplankton stations was compiled from two sources: new samples analyzed and published/unpublished previous records. The updated taxonomic inventory was composed of 39 species of which 3 are new records for the study area. In the case of 22 other species, their known distribution range was expanded. The group richness increased towards low latitudes and with distance from the coast, while the abundance followed the reverse trend. Two faunal areas were defined by multivariate analysis: sub-antarctic area, south of 35° S, with low diversity, and sub-tropical area, more diverse, north of this latitude. These areas coincide with the two major water masses present in the region. Furthermore, the sub-antarctic area was divided into two sub-areas: one covering the shelf waters and the other on the continental slope waters. The shelf sub-antarctic sub-area had the highest abundances of hyperiids formed almost exclusively by T. gaudichaudii species. Particularly, in the southern Patagonian shelf were some of the highest biomass values of T. gaudichaudii throughout its distribution range, mainly during summertime. It is suggested that these large biomasses are the result of a high productivity of this area, and they would be developed by life history adaptation of the individuals to local environmental conditions, particularly food availability and temperature. Thus, the southern Patagonian shelf population of T. gaudichaudii shows a more extended reproductive period, a greater number of annual cohorts and a smaller size at maturity compared with other populations at similar latitudes. The trophic role of T. gaudichaudii in the southern Patagonian shelf food web was assessed from the analysis of stomach contents of 22981 fish, corresponding to 38 species of local fish assemblage, caught in 461 trawl ...